2021
DOI: 10.3389/fendo.2021.589451
|View full text |Cite
|
Sign up to set email alerts
|

Succinate Mediates Tumorigenic Effects via Succinate Receptor 1: Potential for New Targeted Treatment Strategies in Succinate Dehydrogenase Deficient Paragangliomas

Abstract: Paragangliomas and pheochromocytomas (PPGLs) are chromaffin tumors associated with severe catecholamine-induced morbidities. Surgical removal is often curative. However, complete resection may not be an option for patients with succinate dehydrogenase subunit A-D (SDHx) mutations. SDHx mutations are associated with a high risk for multiple recurrent, and metastatic PPGLs. Treatment options in these cases are limited and prognosis is dismal once metastases are present. Identification of new therapeutic targets … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
18
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
6
1
1

Relationship

1
7

Authors

Journals

citations
Cited by 29 publications
(19 citation statements)
references
References 58 publications
0
18
0
Order By: Relevance
“…Succinate buildup stemming from loss of function of SDHx enzyme complex contributes to a plethora of pathophysiological processes. Previously, several downstream effects of succinate accumulation have been linked to altered metabolism, pseudohypoxic HIF1/2 stabilization, oxidative stress, SUCNR1 activation and tumor-associated inflammation (Dahia et al, 2005;Matlac et al, 2021;Pollard et al, 2006). Though these mechanisms have been demonstrated to serve as components in discrete cellular-or disease-specific contexts, their suggested interactions as part of the multistep process of carcinogenesis have not been fully delineated.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Succinate buildup stemming from loss of function of SDHx enzyme complex contributes to a plethora of pathophysiological processes. Previously, several downstream effects of succinate accumulation have been linked to altered metabolism, pseudohypoxic HIF1/2 stabilization, oxidative stress, SUCNR1 activation and tumor-associated inflammation (Dahia et al, 2005;Matlac et al, 2021;Pollard et al, 2006). Though these mechanisms have been demonstrated to serve as components in discrete cellular-or disease-specific contexts, their suggested interactions as part of the multistep process of carcinogenesis have not been fully delineated.…”
Section: Discussionmentioning
confidence: 99%
“…]i homeostasis through autocrine signaling. Specifically, excessive succinate freely shuttles between the mitochondria, cytosol, and across the cell membrane to stimulate the SUCNR1 receptor in SDHx related PC tumors (Matlac et al, 2021).…”
Section: Succinate May Alter [Ca 2+mentioning
confidence: 99%
“…Recently, Wallace et al showed that assessment of Krebs cycle related metabolites by using LC-MS/MS in addition to immunohistochemistry improved the diagnosis of SDH impairment at a functional level (42). These tumoral metabolic pathway alterations translate into characteristic secretory pattern of catecholamine metabolites which contribute to the diagnosis of malignancy (39,(43)(44)(45)(46). Of note, they also appear to have therapeutic relevance (39,(43)(44)(45).…”
Section: Discussionmentioning
confidence: 99%
“…These tumoral metabolic pathway alterations translate into characteristic secretory pattern of catecholamine metabolites which contribute to the diagnosis of malignancy (39,(43)(44)(45)(46). Of note, they also appear to have therapeutic relevance (39,(43)(44)(45).…”
Section: Discussionmentioning
confidence: 99%
“…In addition to being involved in metabolic pathways and energy supply, metabolites trigger oncogenic signalling via noncovalent interactions with macromolecules, mainly involved in competitive inhibition or allostery [ 1 ]. In one noteworthy example, the signalling molecule succinate binds to and activates succinate receptor 1 (SUCNR1) to promote tumour cell proliferation and metastasis [ 6 8 ]. Importantly, metabolites have been shown to possess nonmetabolic functions because of direct protein modifications, which are distinguished from other modifications, such as ubiquitination and sumoylation.…”
Section: Introductionmentioning
confidence: 99%